2017
DOI: 10.25125/engineering-journal-ijoer-jun-2017-12
|View full text |Cite
|
Sign up to set email alerts
|

Additive Manufacturing of PE/Fluorouracil Waffles for Implantable Drug Delivery in Bone Cancer Treatment

Abstract: Abstract-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…Hence, the mechanical strength is directly related to the porosity, as porous printlets present weak interparticular bonding and break easily. This is consistent with previous results on the influence of high laser energy density on improving stiffness of the sintered DDDs [ 55 , 56 , 57 , 58 , 59 , 62 , 63 ]. It is, therefore, necessary to determine the optimal energy interval that balances between the mechanical integrity and stability of the drug [ 60 ].…”
Section: Variability Of the Structuresupporting
confidence: 93%
See 2 more Smart Citations
“…Hence, the mechanical strength is directly related to the porosity, as porous printlets present weak interparticular bonding and break easily. This is consistent with previous results on the influence of high laser energy density on improving stiffness of the sintered DDDs [ 55 , 56 , 57 , 58 , 59 , 62 , 63 ]. It is, therefore, necessary to determine the optimal energy interval that balances between the mechanical integrity and stability of the drug [ 60 ].…”
Section: Variability Of the Structuresupporting
confidence: 93%
“…Previous studies with DDDs have also demonstrated this effect on the printed parts. For instance, Ibuprofen [ 57 ] had a hardening effect because it intensifies sintering, while Hydroxyapatite [ 97 ] and Fluorouracil [ 62 ] decreased the hardness of the DDDs because they space out the polymer particles hindering its continuous melting.…”
Section: Variability Of the Structurementioning
confidence: 99%
See 1 more Smart Citation
“…However, incorporation of an absorbance enhancer could not be required since many biocompatible and biodegradable polymers absorb at the wavelength region of the CO 2 laser, as demonstrated by Salmoria et al [ 21 ]. This research team has printed drug delivery devices (DDDs) with a CO 2 laser using different polymers such as polycaprolactone [ 22 ] and polyethylene [ 23 ]. However, none of the studies conducted with the CO 2 laser on DDDs, evaluated drug stability [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Research in this area has demonstrated the application of SLS in 3D printing of modified-release oral solid dosage forms including orally disintegrating [ 13 ], immediate-release [ 14 , 15 ], and sustained release [ 16 , 17 ] tablets. Moreover, the versatility induced by AM has allowed the printing of multi-material [ 18 ], multi-drug printlets [ 19 ], multi-layered lattices [ 20 ], medical implants [ 21 , 22 , 23 ], and devices [ 24 ]. This previous and currently ongoing research depicts the potential of SLS 3D printing in manufacturing a wide range of robust pharmaceutical dosage forms with different functionalities.…”
Section: Introductionmentioning
confidence: 99%